Ferroelectric and electrical characterization of multiferroic BiFeO3 at the single nanoparticle level - Vasudevan, R. K.; Bogle, Kashinath A.; Kumar, A.; Jesse, S.; Magaraggia, R.; Stamps, R.; Ogale, Satishchandra B.; Potdar, H. S.; Nagarajan, V. (Applied Physics Letters, 2011)
Ferroelectric BiFeO3 (BFO) nanoparticles deposited on epitaxial substrates of SrRuO3 (SRO) and La1-xSrxMnO3 (LSMO) were studied using band excitation piezoresponse spectroscopy (BEPS), piezoresponse force microscopy (PFM), and ferromagnetic resonance (FMR). BEPS confirms that the nanoparticles are ferroelectric in nature. Switching behavior of nanoparticle clusters were studied and showed evidence for inhomogeneous switching. The dimensionality of domains within nanoparticles was found to be fractal in nature, with a dimensionality constant of similar to 1.4, on par with ferroelectric BFO thin-films under 100 nm in thickness. Ferromagnetic resonance studies indicate BFO nanoparticles only weakly affect the magnetic response of LSMO. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3671392]

Azadirachtin a interacts with er alpha domain and regulates bone formation - Kushwaha, P.; Khedgikar, V.; Gautam, J.; Kumar, A.; Thulasiram, Hirekodathakallu V.; Mishra, P. R.; Trivedi, P. K.; Trivedi, R. (Osteoporosis International, 2016)

Influence of kinetic and thermodynamic promoters on post-combustion carbon dioxide capture through gas hydrate crystallization - Kumar, A.; Bhattacharjee, G.; Barmecha, V.; Diwan, S.; Kushwaha, O. S. (Journal of environmental chemical engineering, 2016)
In the present work, we report enhanced kinetics of hydrate formation in the presence of kinetic and thermodynamic promoters, SDS (sodium dodecyl sulphate) and THF (tetrahydrofuran) respectively. Hydrate formation was carried out in a fixed bed reactor for post-combustion capture of CO2. Silica sand was used as a fixed bed medium to capture CO2 from a CO2/N2/SO2 (17.7 mol% CO2, 1.05 mol% SO2 and balance N2) gas mixture by hydrate crystallisation. Experiments were performed at a constant temperature (273.65 K) and at different pressures (9.5 and 2.45 MPa) in batch mode. It was found that the addition of SDS enhances the rate and gas uptake of gas hydrate formation. A higher gas consumption was achieved by using 5.56 mol% THF compared to 1.0 and 3.0 mol% THF.

Assessing therapeutic potential of molecules: molecular property diagnostic suite for tuberculosis - Gaur, A. S.; Bhardwaj, A.; Sharma, A.; John, L.; Vivek, M. R.; Tripathi, N.; Bharatam, P. V.; Kumar, R.; Janardhan, S.; Mori, A.; Banerji, A.; Lynn, A. M.; et al. (Journal of Chemical Sciences, 2017)
Abstract: Molecular Property Diagnostic Suite (MPDS TB) is a web tool (http://mpds.osdd.net) designed to assist the in silico drug discovery attempts towards Mycobacterium tuberculosis (Mtb). MPDS TB tool has nine modules which are classified into data library (1–3), data processing (4–5) and data analysis (6–9). Module 1 is a repository of literature and related information available on the Mtb. Module 2 deals with the protein target analysis of the chosen disease area. Module 3 is the compound library consisting of 110.31 million unique molecules generated from public domain databases and custom designed search tools. Module 4 contains tools for chemical file format conversions and 2D to 3D coordinate conversions. Module 5 helps in calculating the molecular descriptors. Module 6 specifically handles QSAR model development tools using descriptors generated in the Module 5. Module 7 integrates the AutoDock Vina algorithm for docking, while module 8 provides screening filters. Module 9 provides the necessary visualization tools for both small and large molecules. The workflow-based open source web portal, MPDS TB 1.0.1 can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. Graphical Abstract: SYNOPSIS: A web-based MPDS TB Galaxy tool is developed for assessing therapeutic potential of molecules. MPDS TB is categorized into Data Library, Data Processing and Data Analysis. It can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. [Figure not available: see fulltext.] © 2017, Indian Academy of Sciences.
Keywords: chemical analysis; Chemoinformatics; computational chemistry; Diagnosis; Drug discovery portal; Information analysis; Libraries; Molecular graphics; Molecules; Neglected diseases; Open science; Portals; tuberculosis; Web-based technology; Websites

An innovative approach to enhance methane hydrate formation kinetics with leucine for energy storage application - Veluswamy, H. P.; Kumar, A.; Kumar, R.; Linga, P. (Applied Energy, 2017)
Natural gas storage in dathrate hydrates or solidified natural gas (SNG) offers the safest, cleanest and the most compact mode of storage aided by the relative ease in natural gas (NG) recovery with minimal cost compared to known conventional methods of NG storage. The stochastic nature of hydrate nucleation and the slow kinetics of hydrate growth are major challenges that needs to be addressed on the SNG production side. A deterministic and fast nucleation coupled with rapid crystallization kinetics would empower this beneficial technology for commercial application. We propose a hybrid combinatorial approach of methane hydrate formation utilizing the beneficial aspect of environmentally benign amino acid (leucine) as a kinetic promoter by combining stirred and unstirred reactor operation. This hybrid approach is simple, can easily be implemented and scaled-up to develop an economical SNG technology for efficient storage of natural gas on a large scale. Added benefits include the minimal energy requirement during hydrate growth resulting in overall cost reduction for SNG technology.

Nutty carbon: morphology replicating hard carbon from walnut shell for na ion battery anode - Wahid, M.; Gawli, Y.; Puthusseri, D.; Kumar, A.; Shelke, M. V.; Ogale, S. (ACS Omega, 2017)
<div id="absImg" style="position: relative; margin: 0px; padding: 5px; border: 1px solid rgb(204, 204, 204); border-radius: 5px; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; text-align: center; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;"><img alt="Abstract Image" src="http://pubs.acs.org/appl/literatum/publisher/achs/journals/content/acsodf/2017/acsodf.2017.2.issue-7/acsomega.7b00633/20170713/images/medium/ao-2017-00633k_0006.gif" style="border: 0px; max-width: 100%;"> <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Efficient Na ion intercalation/deintercalation in the semigraphitic lattice of a hard carbon derived from the walnut shell is demonstrated. High-temperature (1000 °C) pyrolysis of walnut shells under an inert atmosphere yields a hard carbon with a low surface area (59 m2 g–1) and a large interplanar c axis separation of 0.39–0.36 nm as compared to 0.32 nm for graphite, suitable for Na ion intercalation/deintercalation. A stable reversible capacity of 257 mAh g–1 is observed at a current density of 50 mA g–1 for such nutshell-derived carbon (NDC) with an impressive rate performance. No loss of electrochemical performance is observed for high current cycling (100 mA g–1 → 2 A g–1 → 100 mA g–1). Additionally, the NDC shows remarkably stable electrochemical performance up to 300 charge–discharge cycles at 100 mA g–1 with a minimal drop in capacity.
Keywords: Batteries; Biological and Medicinal chemistry; Biological materials; diffraction; Electric Properties; Electrode-electrolyte interface; spectra; Surface structure; Thermal properties

2D layered transition metal dichalcogenides (MoS2): Synthesis, applications and theoretical aspects - Singh, A.K.; Kumar, P.; Late, D.J.; Kumar, A.; Patel, S.; Singh, J. (Applied Materials Today, 2018)
Recently, graphene and other two-dimensional (2D) transition metal dichalcogenides (TMDCs) have been widely explored due to their unique optical, mechanical, electrical and sensing properties for versatile electronic and optoelectronic applications. The atomically thin layers of TMDC materials have shown potential to replace state-of-the-art silicon-based technology. Graphene has already revealed an excess of new physics and multifaceted applications in several areas. Similarly, mono-layers of TMDCs such as molybdenum disulfide (MoS2) have also shown excellent electrical and optical properties possessing a direct band-gap of ∼1.8 eV combined with high mechanical flexibility. In contrast to semi-metallic graphene, the semiconducting behavior of MoS2 allows it to overcome the deficiencies of zero-band-gap graphene. This review summarizes the synthesis of 2D MoS2 by several techniques, i.e., mechanical and chemical exfoliation, RF-sputtering, atomic layer deposition (ALD) and chemical vapor deposition (CVD), etc. Furthermore, extensive studies based on potential applications of MoS2 such as the sensor, solar cells, field emission and as an efficient catalyst for hydrogen generation has been included. Theoretical aspects combined with the experimental observations to provide more insights on the dielectric, optical and topological behavior of MoS2 was highlighted.

Understanding the behavior of mixtures of protic-aprotic and protic-protic ionic liquids: conductivity, viscosity, diffusion coefficient and ionicity - Thawarkar, S.; Khupse, N. D.; Shinde, D. R.; Kumar, A. (Journal of Molecular Liquids, 2019)
We have investigated the physicochemical properties such as electrical conductivity, viscosity and diffusion coefficient for the binary mixtures of protic ionic liquids with aprotic ionic liquids and of protic with protic ionic liquids at 298.15 K. A significant enhancement in the electrical conductivity is observed for the binary mixtures of ionic liquids, as compared to those of the constituent pure ionic liquids and varied with the composition of the mixtures. The viscosity of binary mixtures of protic with aprotic ionic liquids, 1‑butyl‑3‑methylimidazoliumbis(trifluoromethylsulfonyl)imide [bmIm][NTf2], 1‑butyl‑1‑methylpyrrolidiumbis(trifluoromethylsulfonyl)imide [bmPyrr][NTf2] and 1,3-dimethylimidazolium methyl sulfate, [mmIm][CH3SO4] decreases with an increase in the composition of the [HmIm][CH3COO]. On the contrary, the viscosity for binary mixtures of protic with protic ionic liquid, 1‑methylpyrrolidium acetate [HmPyrr][CH3COO] and 4‑methylmorpholine acetate [HmMorph][CH3COO] increases upon the addition of 1‑methylimidazolium acetate [HmIm][CH3COO]. The self diffusion coefficients were determined for all the binary mixtures of ionic liquids by using Pulsed Gradient Spin Echo (PGSE) NMR method. Self diffusion coefficients of [bmIm][NTf2]-[HmIm][CH3COO], [bmPyrr][NTf2]-[HmIm][CH3COO], [mmIm][CH3SO4]-[HmIm][CH3COO] are enhanced, while those of [HmPyrr][CH3COO]-[HmIm][CH3COO] and [HmMorph][CH3COO]-[HmIm][CH3COO] decreases on addition of [HmIm][CH3COO]. This is converse in the case of viscosity. Furthermore, the above correlations were interpreted with the help of NMR spectroscopy on the basis of interactions of ions in the binary mixtures of ionic liquids. Finally, we have quantified the ionicity through the Nernst–Einstein equation and have confirmed the validity of the Walden rule for the binary mixture of ionic liquids.